RETROSPECTIVE ANALYSIS OF FETOPLACENTAL DYSFUNCTION IN PREGNANT WOMEN WITH CORONAVIRUS INFECTION - Kholova, Z.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. Fetoplacental dysfunction (FPD) is a general term that describes some disorders of the interaction between the fetus and the placenta, which can lead to various complications of pregnancy and the birth of premature or sick children. The purpose of the study to study the frequency and risk factors of fetoplacental dysfunction in pregnant women with COVID-19. Materials. The study included 100 pregnant women who underwent COVID-19 in various stages of pregnancy. The study was conducted in the period from 2021 to 2022 in the obstetric complex No. 3.Tashkent. A retrospective study of cases of fetoplacental dysfunction was conducted in 100 pregnant women, 50 in the second trimester and 50 in the third trimester of pregnancy. Results. As a result of the study, we found that 80% of pregnant women with COVID-19 had a deterioration in fetoplacental function during pregnancy. The frequency of fetoplacental dysfunction in the second trimester was 43% in the third trimester in 37% of pregnant women. Analysis of the outcomes of childbirth in women with fetoplacental dysfunction on the background of COVID-19 showed that 27% of women had children born with low weight, 31% had asphyxia of varying severity. Conclusion. COVID-19 can cause deterioration of fetoplacental function in 80% of pregnant women in the second and third trimesters of pregnancy. The frequency of fetoplacental dysfunction in the second trimester was 43% in the third trimester in 37% of pregnant women. An analysis of the outcomes of childbirth in women with fetoplacental dysfunction against the background of COVID-19 showed that 27% of women had children born with low itch, 31% had asphyxia of varying severity.